The Four Risk of International Business Mc Donald’s dalam Pemasaran Global - Cindy Cindy; Cristina Cristina; Thalia Wang; Dennys Ng; Jeffrey Andelson (Universitas Muhammadiyah Makassar, 2024)
As time goes by and the development of the business being undertaken, of course the opportunities for expansion will also be higher. Mc Donald's is one of the multinational companies engaged in the fast food sector and has been known by many people who have finally expanded globally. The purpose of this research is to identify and analyze the four risks faced in international business or the four risks of international businesses that have Mc Donald's. The research method that we use is qualitative method, observation and internet searching. Observation of Mc Donald's uses a qualitative method, namely the four risks of international business which consist of cross cultural risk, country risk, currency risk, financial, and commercial risk. Mc Donald's in dealing with cultural differences in expanding business to other countries is by studying the culture implemented by the country to maintain its success. Mc Donald's provides services by meeting consumer needs by considering local, demographic and geographical factors of the country. Mc Donald's must give a good impression and find out whether the cooperation partners can create good cooperation in the company's operations. McDonald's has the best fast food chain management in its business as well as being a pioneer in a global marketing strategy, implementing a certain system that is adapted to the region where the McDonalds's store is located. McDonald''s success in the fast food industry is due to its ability to adapt not only locally but on a global scale